PENGGUNAAN MEDIA PAPAN FLANEL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK KELOMPOK B - Widiastuti, Widiastuti; Adawiyah, Rini Robiatul; Jaya, Ilham; Yurita, Hestilia Oktama (Jurnal Anak Bangsa, 2024)
This research aims to describe the use of flannel boards to improve children's early reading abilities. The research method used is descriptive in the form of Classroom Action Research. The subjects in this research were 15 children. The results of data analysis show that: 1) learning planning such as determining learning materials and formulating objectives, developing and organizing learning media, planning class management, and preparing learning plan assessment tools, 2). Learning steps include: conducting learning, carrying out assessments of learning processes and outcomes, 3). Increased ability with indicators: sticking words (e.g. sun, earth, etc.) on the flannel board, reading words (e.g. stars, moon, etc.) on the flannel board, arranging the same initial words on the flannel board (e.g. moon, stars and hills)